Transforming Sustainability: The Role of Transformational Leadership and Knowledge in Disruptive Innovation - Auliasari, Ria Windi; Santoso, Adi; Setiawan, Fery (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
In Indonesia, educators have made notable strides in advancing their teaching methodologies. The research conducted was a quantitative study with a total of 118 university lecturers in East Java using a purposive sampling technique by distributing questionnaires using a Likert scale. SMART-PLS 3 is used as an analysis tool with PLS-SEM. This study found that transformational leadership has a positive and significant effect on disruptive innovation (T= 3.564, β= 0.285, P= 0.000). Transformational leadership has a positive and significant effect on knowledge acquisition ability (T= 13.110, β= 0.645, P= 0.000). Transformational leadership has a positive and significant effect on the ability to share knowledge (T= 11.940, β= 0.617, P= 0.000). The ability to acquire knowledge has a positive and significant effect on disruptive innovation (T= 2.481, β= 0.274, P= 0.011). The ability to share knowledge has a positive and significant effect on disruptive innovation (T= 2.994, β= 0.273, P= 0.003). Knowledge acquisition ability mediates the relationship between transformational leadership and disruptive innovation (T= 2.396, β= 0.177, P=0.177). Knowledge-sharing ability mediates the relationship between transformational leadership and disruptive innovation (T=3.052, β=0.169, P=0.002). These findings contribute to the theory of transformational leadership regarding the most effective leadership style in influencing the improvement of knowledge sharing ability, knowledge acquisition ability and disruptive innovation. Researchers found a lack of research linking transformational leadership and radical innovation. This is what encourages research to be carried out in the hope of novelty and the development of research on leadership theory.